2017
DOI: 10.1016/j.neurobiolaging.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin 1 mutations influence processing and trafficking of the ApoE receptor apoER2

Abstract: Presenilin (PS)-1 is an intramembrane protease serving as the catalytic component of γ-secretase. Mutations in the PS1 gene are the most common cause of familial Alzheimer’s disease (FAD). The LDL-receptor family member apoER2 is a γ-secretase substrate that has been associated with AD in several ways, including acting as a receptor for apolipoprotein E. ApoER2 is processed by γ-secretase into a C-terminal fragment (γ-CTF) that appears to regulate gene expression. FAD PS1 mutations were tested for effects on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Interestingly, apoE3 and apoE4 consistently inhibited reelin from binding to VLDLR and apoER2; this study also indicated that apoE interfered with the ability of reelin to activate a Dab1-dependent signaling pathway [ 12 ]. A later study also saw that, unlike reelin, apoE failed to elevate apoER2 processing [ 65 ], whereas others have found that the Dab1-dependent pathway was activated by apoE [ 66 ] and that apoE and apoER2 co-localized in endosomes [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, apoE3 and apoE4 consistently inhibited reelin from binding to VLDLR and apoER2; this study also indicated that apoE interfered with the ability of reelin to activate a Dab1-dependent signaling pathway [ 12 ]. A later study also saw that, unlike reelin, apoE failed to elevate apoER2 processing [ 65 ], whereas others have found that the Dab1-dependent pathway was activated by apoE [ 66 ] and that apoE and apoER2 co-localized in endosomes [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…T98G cells were obtained from American Type Culture Collection. Stable transformants were generated as described previously by Wang et al [23]. Recombinant apoE was prepared under native conditions with the intention of retaining any lipid content present.…”
Section: Methodsmentioning
confidence: 99%
“…ApoE was purified from conditioned medium of T98G-apoE3-expressing or T98G-apoE4-expressing cells, as described in Wang [23]. ApoE proteins (50 ng) were mixed with BSA (5 μg) and incubated under conditions described by Mao et al [27] with a 32 P-labeled dsDNA probe containing either the CLEAR sequence (5′-GTA GGT CAC GTG ACC GGG-3′) or a scrambled sequence (5′-GTA GGT CTG CAG ACC GGG-3′).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to Reelin itself, gene polymorphism studies point to the possibility that variations of the ApoER2 gene are also associated with development of AD [ 131 ]. ApoER2 association to AD was also recently reported by a study showing that ApoER2 trafficking and processing is influenced by mutations in the presenilin 1 gene identified as risk factor for familial AD [ 132 ]. Indeed, the processing of ApoER2 is changed in AD patients in a way that less ApoER2-CTF fragments are produced [ 133 ].…”
Section: Reelin Apoer2 and Vldlr In Alzheimer’s Diseasementioning
confidence: 68%